Sticky platelet: A practical literature review. - Arboleda-Rojas, Manuela (2022)
Introduction: Sticky platelet syndrome is an autosomal dominant disease, with qualitative effects on platelet activity with increased aggregation in response to low concentrations of platelet agonists such as: epinephrine, adenosine diphosphate (ADP), or both. It is an uncommon disease, however, its prevalence is higher in women and with a higher risk in pregnant women. Objective: To perform a practical review on sticky platelet syndrome, emphasizing aspects related to genetic variability and the molecular area, in order to avoid thrombotic events. Materials and methods: A literature search was performed, especially original research articles in MEDLINE, EMBASE, Lilacs and Science Direct from 1962 to 2019, in order to update information especially in pregnant women. Characteristics of genetic mutations and molecular alterations in sticky platelet syndrome that are closely related to thrombotic events and fetal loss are described. Conclusion: It is important to follow up patients carefully in order to detect the disease in time and to be able to perform an effective treatment in a timely manner, avoiding complications.